2002
DOI: 10.1002/1521-3846(200205)22:1/2<121::aid-abio121>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Both Different Light Conditions and the pH Value on the Capacity of Salvinia minima Baker for Removing Cadmium, Lead and Chromium

Abstract: SummarySalvinia minima is a tropical aquatic floating plant, which has become a weed in the tropical and subtropical regions due to its high productivity and tolerance to a wide range of temperatures. The objective of this work was to evaluate the effect of two different light conditions (extreme light limiting conditions and non-limiting light conditions) and the pH (at different values, depending on the metal) on the capacity of Salvinia minima BAKER for accumulating and removing Cd (II), Pb (II) and Cr (VI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 16 publications
4
22
0
3
Order By: Relevance
“…Therefore, plants may have possibly been in contact with a higher concentration of copper in its free ionic form during the first minutes to hours of the bioassay. Studies on the kinetics of heavy metals uptake by aquatic plants have revealed an initial phase of fast metal removal followed by a lineal slower phase [23] and, in accordance with this, [4] found that S. minima lead and cadmium uptake was 55 % and 60 %, respectively, during the first 4 to 6 hours of their bioassay. May S. minima's copper removal uptake been higher without metal precipitation?…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Therefore, plants may have possibly been in contact with a higher concentration of copper in its free ionic form during the first minutes to hours of the bioassay. Studies on the kinetics of heavy metals uptake by aquatic plants have revealed an initial phase of fast metal removal followed by a lineal slower phase [23] and, in accordance with this, [4] found that S. minima lead and cadmium uptake was 55 % and 60 %, respectively, during the first 4 to 6 hours of their bioassay. May S. minima's copper removal uptake been higher without metal precipitation?…”
Section: Discussionsupporting
confidence: 59%
“…In the control group, metal concentration was below the method detection limit. During the first few hours from the beginning of the bioassay, water in treatments T 4 and T 5 turned light blue. This indicated copper precipitation as a colloide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ramets were cultivated in a greenhouse for 5 days, in pots with 25 L of Hogland's nutrient solution with pH between 6.5 and 7, with 1/5 of the original ionic strength (Hoagland and Arnon, 1950). The pH value was determined according to Olguín et al (2002). During the experimental period the average temperature was 21.9 °C.…”
Section: Bioassay Setupmentioning
confidence: 99%
“…Plants must have a great capacity to tolerate and transform to less toxic forms and/or accumulate the pollutant to be removed [6,7]. Wastewater treatment by means of phytoremediation involves either the use of aquatic floating plants in ponds [8,9] or the use of emergent aquatic plants in constructed wetlands [10]. Constructed wetlands have been sporadically applied for the treatment of acid drainages in mines, as well as in the minimisation and control of water pollution in general.…”
Section: Introductionmentioning
confidence: 99%